Developing reflective dispositions through collaborative knowledge-building during small group Bible study - Toh, Tze Keong (International journal of Christianity & education, 2017)
This article explores the use of a constructivist pedagogical approach to cultivate reflective dispositions during small group Bible study. Conducted in a local church Bible class setting (n = 12), the instructional design emulated the reflective thinking process, while adopting collaborative knowledge-building as its pedagogical framework. Results showed that the participants exhibited dispositions of reflective thinking in terms of open-mindedness, rootedness and responsibility in the social learning environment. Results also showed that participants were more confident of their own beliefs at the end of the course, and arrived at the desired biblical understanding with respect to the study topic.